Total arsenic in aquatic organisms collected from south-central Puget Sound urban lakes between 2004 and 2019 - Erin A Hull; Rebecca B Neumann; Julian D Olden; James E Gawel (PANGAEA, 2021)
Snail (Bellamya chinensis), crayfish (Pacifastacus leniusculus; Procambarus clarkii), and sunfish (Lepomis gibbosus; L. macrochirus) sampling occurred primarily over four dates in June 2019 in the entire nearshore (< 2 m depth) area of each lake. Additional frozen crayfish samples from Killarney, Steel, and Pine Lakes collected in 2004, 2009, 2017, and 2018 were also analyzed. All crayfish were captured using minnow traps set overnight and baited with dog kibble. Snails were collected by hand via snorkeling or with a dip net from a boat. Sunfish were collected using beach seining. Snails, crayfish, and fish were euthanized and dissected for edible tissues (whole snail, excluding shell, crayfish tail meat, and fish muscle tissue (fillet)). Duplicate portions of each edible tissue of snail, crayfish, or fish specimen were dried at 60 °C overnight. Dried samples were homogenized using a porcelain mortar and pestle. Oven-dried animal tissues were digested using a microwave-assisted (CEM MARS 5) total digestion protocol (modified EPA method 3015a). Concentrations of total arsenic in digested animal tissue samples were determined by inductively-coupled plasma mass spectrometry (ICP-MS) on an Agilent 7900 at the University of Washington Tacoma.